A new solution for radiation transmission in anti-scatter grids. (21st September 2016) - Zhou, Abel; Yin, Yuming; White, Graeme L; Davidson, Rob
Abstract: Analytic calculations of radiation transmission in focused grids or parallel grids are currently performed using the Day and Dance method. In parallel grids, this method calculates the mean transmission of radiation of grid units each of which consists of a strip and the adjacent interspace. The Day and Dance method extrapolates grid-unit-mean transmission of uniformly distributed radiation in focused grids and may underestimate the transmission of scatter radiation. This method fails to preserve detailed grid strips and interspaces information resulting from stationary grids. In this work a new method has been developed to calculate transmission of radiation. This new method and that of Day and Dance were evaluated and compared using Monte Carlo simulation. In the moving grids, the new method calculated the transmission of radiation and accounted for the effect of grid cut-off, which is approximately 4% in the transmission of primary radiation for the mammographic grid (grid ratio 5:1) or 7% for the general grid (grid ratio 15:1). In stationary grids, the new method preserves grid strips and interspace information—observed as grid lines in the x-ray image. The new method improves modelling of radiation transport in focused or parallel grids—whether moving or in stationary—over other analytical methods currently in use.